Clinical neuropsychology - Heilman, Kenneth M., 1938-; Valenstein, Edward, 1942- (New York : Oxford University Press, 2012)
- Aphasic syndromes / David Caplan##- Phonology, semantics, and lexical semantics / Stephen E. Nadeau and Diane L. Kendall##- Syntactic aspects of language disorders / David Caplan##- Acquired dyslexia / H. Branch Coslett##- Agraphia / David P. Roeltgen and Lauren Ullrich##- Disorders of visual-spatial perception and cognition / Martha J. Farah and Russell A. Epstein##- Acalculia and disturbances of the body schema / Natalie L. Denburg and Daniel Tranel##- Anosognosia / John C. Adair and Anna M. Barrett##- Apraxia / Kenneth M. Heilman and Leslie J. Gonzalez Rothi##- Agnosia / Russell M. Bauer##- Neglect and related disorders / Kenneth M. Heilman, Robert T. Watson, and Edward Valenstein##- Callosal syndromes / Eran Zaidel, Marco Iacoboni, Steve Berman, Dahlia W. Zaidel and Joseph E. Bogen##- The frontal lobes / Antonio R. Damasio, Steven W. Anderson, and Daniel Tranel##- Emotional disorders associated with neurological diseases / Kenneth M. Heilman, Lee X. Blonder, Dawn Bowers, and Edward Valenstein##- Amnesic disorders / Russell M. Bauer, Gila Z. Reckess, Abhay Kumar, and Edward Valenstein##- Neuropsychology of dementia / David Knopman##- Creativity / Valeria Drago, Bruce Miller, and Kenneth M. Heilman.
Includes bibliographical references and index.
boek